Concrete, bollards, and fencing: exploring the im/mobilities of security at public events in Brisbane, Australia. Issue 1 (1st January 2022) - Dorreboom, Matthew; Barry, Kaya
ABSTRACT: Large public inner-city events require a significant amount of temporary security infrastructures and altered mobility designs to safely facilitate the movement of the public throughout already highly mobile spaces. Recent security risks from vehicle attacks have resulted in increased security in order to mitigate potential threats. Issues arise as increased security infrastructures interrupt and redirect pedestrian mobility, reconfiguring traditionally 'safe' pedestrian and leisure spaces into 'unsafe' spaces under the pre-emptive atmosphere of unknown threats. This paper explores how im/mobilities arise through increased security during fireworks events in Brisbane, Australia. Using ethnographic observation and visual documentation of crowd movements, we critically examine the temporal alterations to wayfinding and mobility infrastructures. Although increased security serves to foster a safe and secure environment, we suggest that the altered mobilities and heightened visibility of security risks impacting on the overall festive atmosphere of the events.